The institutionalisation of the social and solidarity economy in France as a meso-space - Sylvain Celle (Revue de la Régulation)
Nowadays, the social and solidarity economy (SSE) is seen as a relatively specific economic system within contemporary economies. Despite a relative lack of interest in the SSE, certain “institutional” economists—in particular regulationists–have underlined its specificity within an array of various institutional arrangements in capitalist economies. More specifically, regulationist studies view the SSE, or some of its components at least (e.g., cooperatives, mutual insurance, etc.) as relatively autonomous meso-economic spaces within capitalist regimes. From this perspective, this article aims to shed light on how the SSE has become, over time, a relatively unified and autonomous meso-economic space around three main periods, corresponding to three historical compromises of the SSE as a meso-space with regard to its constituent elements (entities, legal rules, ideologies, etc.) and its integration into the evolution of French capitalist regimes. The first (liberal) compromise (1790–1880) was characterised by the emergence of the original, fragmented SSE entities, in a regime dominated by economic liberalism. The second (republican) compromise (1880–1970) saw the institutionalisation and division of large SSE “families” (e.g., cooperatives, mutual insurances, associations) under the guidance of the social state. The third (neoliberal) compromise (since 1970) reflects the recent unification and institutionalisation of the SSE as a meso-economic space, but whose unity and autonomy in the face of contemporary capitalist pressures remain fragile.